Pengaruh Self-Disclosure Terhadap Komunikasi Interpersonal Kepada Orang Tua Pada Remaja Akhir Di Kota Banjarmasin - Saputri, Desi Alam; Aprianty, Rizqi Amalia; Fitriah, Aziza (Innovative: Journal Of Social Science Research, 2025)
Interpersonal communication is an interaction between two people or a small group of people with some feedback effects. Self-disclosure has great benefits in improving self-understanding. Honest and open self-disclosure allows individuals to reflect on and evaluate their feelings and thoughts more clearly. This study aims to determine the effect of self-disclosure on interpersonal communication between parents and late adolescents in the city of Banjarmasin. This study employs a quantitative method with a correlational approach. The population was determined by the Central Statistics Agency to be 1,092,878, with the research sample consisting of 100 respondents aged 18–21 years. Data collection utilized a Likert scale with incidental sampling techniques, analyzed using simple linear regression analysis. The analysis results indicate a significant positive influence between self-disclosure and interpersonal communication, with a result of 0.567. This means that the higher the self-disclosure, the better the quality of interpersonal communication. The frequency distribution of both variables resulted in a moderate category.